Effects of nitrogen application frequency via subsurface drip irrigation on corn development and grain yield. (9th November 2016) - van Donk, Simon J.; Shaver, Tim M.
ABSTRACT: Subsurface drip irrigation (SDI) has not only potential for water conservation, but also for improving nutrient use efficiency. Two nitrogen (N) application frequencies (every week versus every two weeks, via SDI) were compared in 2012 and 2013 on a Cozad silt loam in North Platte, Nebraska. The weekly treatment was fertigated every week for seven weeks in a row; the bi-weekly treatment was fertigated in weeks 1, 3, 5 and 7. Both treatments received the same total amount of N. There was a positive grain yield response to N application, but no advantage was found to a greater frequency of N application. Corn ( Zea mays L.) grain yields and other indicators of corn growth and development (canopy-intercepted light, vegetation indices, indicators of chlorophyll content of corn plant leaves) were not affected by N application frequency.